Socio-Demographic and Anthropometric Profile of Diabetic Patients Attending Diabetes Clinic in Tertiary Care Hospital of Central Gujarat - Himanshu M Rana; Parag Chavda; Chirag C Rathod; Meera Mavani (Medsci Publications, 2015)
Background: With a rise in non communicable diseases in India, di- abetes has been a modern epidemic showing a rising trend in Gujarat also. A large number of diabetes patients come to the diabetes clinic of our tertiary care hospital in Central Gujarat. The large proportion of patients presenting with this condition prompted us to look at the profile of such patients. Methods: This was a descriptive hospital-record based cross sectional study involving a total of 167 diabetic patients enrolled in the di- abetes clinic from November 2014 to December 2014. The data was entered and then analyzed in Microsoft excel sheet. Results: Among the 167 study participants, we found that 85 were males and 82 were females. It was more common among those above age of 60 years followed by 51-60 years. Almost 60% had uncon- trolled diabetes. Nearly 60% of the diabetic patients were hyperten- sive. Almost 3/4th of the patients had high waist hip ratio and 21% patients were obese. Conclusion: The diabetic patients presenting to this tertiary care hospital belong to both genders and are from lower socioeconomic strata and having limited education in their geriatric age group. There is high proportion of obesity and hypertension among them.